The Metabolic Changes between Monolayer (2D) and Three-Dimensional (3D) Culture Conditions in Human Mesenchymal Stem/Stromal Cells Derived from Adipose Tissue - Paulina Rybkowska; Klaudia Radoszkiewicz; Maria Kawalec; Dorota Dymkowska; Barbara Zabłocka; Krzysztof Zabłocki; Anna Sarnowska (Cells, 2023)
Introduction: One of the key factors that may influence the therapeutic potential of mesenchymal stem/stromal cells (MSCs) is their metabolism. The switch between mitochondrial respiration and glycolysis can be affected by many factors, including the oxygen concentration and the spatial form of culture. This study compared the metabolic features of adipose-derived mesenchymal stem/stromal cells (ASCs) and dedifferentiated fat cells (DFATs) cultivated as monolayer or spheroid culture under 5% O2 concentration (physiological normoxia) and their impact on MSCs therapeutic abilities. Results: We observed that the cells cultured as spheroids had a slightly lower viability and a reduced proliferation rate but a higher expression of the stemness-related transcriptional factors compared to the cells cultured in monolayer. The three-dimensional culture form increased mtDNA content, oxygen consumption rate (OCR) and extracellular acidification rate (ECAR), especially in DFATs-3D population. The DFATs spheroids also demonstrated increased levels of Complex V proteins and higher rates of ATP production. Moreover, increased reactive oxygen species and lower intracellular lactic acid levels were also found in 3D culture. Conclusion: Our results may suggest that metabolic reconfiguration accompanies the transition from 2D to 3D culture and the processes of both mitochondrial respiration and glycolysis become more active. Intensified metabolism might be associated with the increased demand for energy, which is needed to maintain the expression of pluripotency genes and stemness state.